Systematic Literature Review: PjBL-STEM in Higher Education Physics Learning for Students’ Cognitive Development (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2025)
The digital transformation in the Education 4.0 era demands innovative learning strategies that foster students’ cognitive development. This study systematically reviews the implementation of the STEM-based Project-Based Learning (STEM-PjBL) model in higher education physics courses. The research method applied was a Systematic Literature Review (SLR) guided by the PRISMA framework, with literature searches conducted through Scopus, ScienceDirect, and Google Scholar. From an initial 50 articles, 25 were selected for qualitative descriptive analysis. The findings indicate that STEM-PjBL positively impacts students’ cognitive development, critical thinking, and collaborative skills. However, challenges such as limited resources and educators’ readiness remain significant obstacles. Overall, STEM-PjBL holds great potential as an innovative instructional approach for higher education in the digital era.Keywords: STEM-PjBL, physics learning, higher education, cognitive development